Adsorption behavior and mechanism of CO2 in the Longmaxi shale gas reservoir. Issue 40 (13th September 2022) - Xie, Weidong; Wang, Meng; Vandeginste, Veerle; Chen, Si; Yu, Zhenghong; Wang, Jiyao; Wang, Hua; Gan, Huajun
Abstract : The micropore filling mainly occurs in micropores, including the slit, capillary and ink-shaped pores. Molecular layer adsorption mainly occurs in mesopores and macropores, including the slit, plate, capillary and ink-shaped pores. Abstract : CO2 is the main greenhouse gas in Earth's atmosphere, and has been causing global warming since the industrial revolution. Therefore, technologies to mitigate carbon emissions have attracted extensive research. Shale gas reservoirs could serve as potential sequestration space for CO2 . This paper aims to gain insight in the CO2 adsorption behavior and mechanism in Longmaxi shale. The micropore filling theory is the best model for CO2 adsorption in the shale samples with the smallest MSR (Mean Square of Residual). This model fits better than that of the monolayer adsorption and multi-layer adsorption theories. Specifically, micropore filling adsorption mainly occurs in micropores, including the closed end of slit pores, capillary pores, and ink-shaped pores. Molecular layer adsorption mainly occurs in mesopores and macropores, including the open end of slit pores, plate pores, capillary pores, and ink-shaped pores. Moreover, the prediction model of CO2 storage quantity in deep shale gas reservoirs of China is established. This model shows that 91.5–388.89 × 10 12 m 3 of CO2 could in theory be stored in an adsorbed state. CO2 is mostly stored by an adsorbed state (higher than 95%) and a free state with good security and low leakage risk. The results from this work are of specific interest for global research on CO2 adsorption characteristics and adsorption mechanisms in different pore structures. Furthermore, it provides certain guidance for geological storage of CO2 in shale.